Golden Excess : Art and the Aesthetics of the Incredible in Neronian Rome - Varner, Eric R. (Brill's Studies on Art, Art History, and Intellectual History, 2025)
Golden Excess: Art and the Aesthetics of the Incredible in Neronian Rome is the first monograph to offer a full art historical synthesis of the rich archaeological and monumental evidence for Nero's remarkable principate. An outsized and innovative artistic program emerges, informed by aesthetics of excess, the grotesque and learned luxury, that rivals the cultural achievements of Rome's first emperor, Augustus and stands in stark contrast to the universally negative and disparaging accounts of Nero in ancient authors. Indeed, Neronian Rome witnessed an astonishing efflorescence in the arts whose lasting effects still resonate.